Factors Affecting Levels of International Cooperation In Carbon Abatement Projects - Dinar, Ariel, 1947- 1947- (The World Bank, 2008)
The Clean Development Mechanism, a provision of The Kyoto Protocol, allows countries that have pledged to reduce their greenhouse gas emissions to gain credit toward their treaty obligations by investing in projects located in developing (host) countries. Such projects are expected to benefit both parties by providing low-cost abatement opportunities for the investor-country, while facilitating capital and technology flows to the host country. This paper analyzes the Clean Development Mechanism market, emphasizing the cooperation aspects between host and investor countries. The analysis uses a dichotomous (yes/no) variable and three continuous variants to measure the level of cooperation, namely the number of joint projects, the volume of carbon dioxide abatement, and the volume of investment in the projects. The results suggest that economic development, institutional development, the energy structure of the economies, the level of country vulnerability to various climate change effects, and the state of international relations between the host and investor countries are good predictors of the level of cooperation in Clean Development Mechanism projects. The main policy conclusions include the importance of simplifying the project regulation/clearance cycle; improving the governance structure host and investor countries; and strengthening trade or other long-term economic activities that engage the countries